Analisis Parameter Fisika dan Kimia Air Bersih di Desa Lalumpe Kecamatan Kombi Kabupaten Minahasa - Vlagia Indira Paat; Anderson Arnold Aloanis; Andre Karundeng (Jurnal Kimia Fullerene, 2018)
A research on physical and chemical parameters on clean water in Lalumpe village, Kombi district has been done. . Water sampling is done by purposive sampling method. Samples were taken 2 times and then analyzed the physical and chemical parameters in the laboratory of Balai Teknik Kesehatan Lingkungan dan Pemberantasan Penyakit Menular Kelas 1 Manado. From the research results, clean water samples are categorized well and feasible to use because all parameters both physics and chemistry are analyzed below the threshold quality standard required based on the standard of environmental health standard for water media for sanitary hygiene purposes